MANAJEMEN RUANG GTK DALAM MENINGKATKAN KOMPETENSI GURU DI SD NEGERI 1 CIKERIS (Studi Kasus di SD Negeri 1 Cikeris Kabupaten Purwakarta) - Umara, Rohmat; Hidayat, Pian Firman; Nurmilah, Irma; Syuhada, Imam; suwandari, Lilis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the management of the Ruang GTK (Teacher and Education Personnel Room) in improving teacher competence at SD Negeri 1 Cikeris, Purwakarta. This research is motivated by the phenomenon of the underutilization of the Ruang GTK platform at the elementary school level due to limited digital literacy, inadequate facilities, and weak organizational and supervisory systems at the school level. The study employs a qualitative approach with a case study method to explore planning, organizing, implementing, and supervising activities related to the Ruang GTK management. Data were collected through interviews, observations, and document analysis, then analyzed using an interactive model. The results show that the planning of Ruang GTK activities is already aligned with teachers’ professional development needs but lacks a systematic needs assessment. The organizing aspect is still informal without clear task distribution and structured organizational roles. Implementation of activities runs well and is well-received by teachers, though constrained by limited facilities and infrastructure. Supervision has been carried out informally but lacks a structured evaluation system. Overall, the management of Ruang GTK at SD Negeri 1 Cikeris shows potential as a strategic medium for teacher professional development if strengthened with systematic planning, formal organizing, adequate facilities, and measurable evaluation mechanisms. Keywords: management, Ruang GTK, teacher competence, elementary school, professional development